Failure mechanics mechanisms and permeability stage evolution of limestone considering wave velocity and failure surface characteristics - Wu, Genshui; Yu, Weijian; Pan, Bao; Fang, Chuangfeng; Guo, Hanxiao; Zhang, Chao (Soils and Foundations, 2025)
•The macroscopic mechanical and wave velocity characteristics of limestone and sandstone were investigated.•Nuclear magnetic resonance techniques were used to reveal the microscopic fracture distribution features in rocks .•A rock stress-permeability phase evolution characteristics that considers confining pressure factors was developed. This research aims to investigate the impact of seepage conditions on the macroscopic and microscopic failure mechanics mechanisms of deep coal seam floor rock mass. The deep coal seam mining floor rock mass in North China has been penetrated by groundwater for a long period in a high-temperature and high-pressure environment, and its mechanical behavior is complicated and diversified. The macro- and micro-mechanical behavior of rock failure under seepage conditions was investigated in this work on deep floor rock strata using experimental methods such as rock mechanics, wave velocity, and nuclear magnetic resonance. The results demonstrate that the original cracks in thin limestone are more developed and have a gully-like structure at the mesoscopic scale than those in Ordovician limestone. According to the nuclear magnetic results, as the confining pressure increases, the initial water-conducting fissures and expanded cracks in the thin limestone may be constricted or closed. Macroscopically, under the action of stress and seepage in different types of rocks, fissures provide the main seepage channels. Due to the confining pressure, the pores are compressed and the permeability decreases significantly. Because rock permeability varies with confining pressure and axial pressure, there is a stress threshold for penetration mutation at each stage. The linear and nonlinear stage evolution characteristics of deep rock permeability and stress with confining pressure are established. The confining pressure affects the internal pore and crack structure of the rock, generating complex seepage network channels and causing changes in permeability properties. The research results provide a scientific foundation and theoretical support for the safe design and sustainable development of underground engineering.